Introduction and critical framework - Luigi Bartolomei (In_Bo, 2015)
This special edition of our department journal is dedicated to a wide range inquiry in making and teaching architecture today. It is a global investigation primarily for the authors, both professionals and professors that this issue boasts, who in their contributions have managed to compose a fresco on architecture’s conditions in the “two wests” at each side of the Atlantic.